Implementasi Pengajuan Penurunan PPh Pasal 25 : Tahun 2020-2024 di Indonesia (Systematic Literature Review) - Hasanah, Noor; Kolin, Maria Delastrada Rina; Noval A, Muhamad; Wahono, Puji; Pahala, Indra (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
The rules and procedures for filing income tax relief have been regulated by the government in Article 25. The purpose of this study was to determine how the process of filing an application for reduction of income tax installment Article 25. Taxpayers can file if they experience: a significant decrease in income, business losses, unexpected expenses, and certain events that cause OP taxpayers to experience financial difficulties. Although it has been regulated, problems and knowledge gaps still occur among taxpayers. This causes the potential for reduced state tax revenue and Taxpayers entitled to a decrease in Income Tax Article 25 can not take advantage of their rights. Therefore, research related to this theme is needed, to understand the applicable tax provisions and fulfill their obligations in paying Article 25 Income Tax in an orderly and timely manner.